THE EFFECTS OF CRIMINAL LAW ON LEGAL SUBJECTS OF WASTE MANAGEMENT THAT DAMAGES THE ENVIRONMENT - Sunariyo; Hasibuan, Imelda (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Article 28H of the 1945 Constitution of the Republic of Indonesia establishes constitutional and human rights for all citizens, outlining principles for managing the environment. These principles include state responsibility, justice, and sustainability. Despite the constitutional emphasis on the right to a good and healthy environment, environmental crimes are prevalent in Indonesia, particularly where companies dispose of waste directly into rivers, leading to pollution. While Article 28H, paragraph (1) underscores the right of individuals to live prosperously in a physically and mentally healthy environment, the reality contradicts these rights. Business activities in certain regions, especially along rivers, do not align with these principles. The prevalent criminal acts often involve improper waste disposal into rivers, causing environmental degradation. It is essential to consider Law No. 32 of 2009 on Environmental Protection and Management to tackle these challenges. According to Article 1, 14 of this legislation, environmental pollution is defined as human activities leading to the introduction or involvement of living beings, substances, energy, or other environmental elements, exceeding the quality standards set for environmental conditions. This study employs a normative juridical research method that incorporates three distinct approaches. The first approach is the statutory approach, involving a thorough examination of legal regulations relevant to the central focus of the research. The second approach, the conceptual approach, involves comprehending the legal concepts that underlie the research, including the values ​​inherent in the norms. Lastly, the case approach analyzes legal norms or principles applicable to Environmental Criminal Offenses, encompassing regulations, accountability, and possible legal consequences. Environmental pollution can be explained based on Article 1, number 14 of Law No. 32 of 2009 concerning Environmental Protection and Management.